Geometric interpretation of integrals - Puriuškis, Gintaras (Lietuvos matematikos rinkinys, 2010)
There are considered the geometric interpretation of curvilinear intels of first and second type. The integrals first type are interpretated like area of cilindric figure, the integrals of second type – like area of projection of the same cilindric figure to the coordinate plane.
Keywords: geometric interpretation; curvilinear integral